Manual Saliran Mesra Alam (MSMA): Should urban planners be aware of it? - Majid, M. Rafee; Chong, Chiew Chia (2008)

(untitled)
It has been more than seven years since Manual Saliran Mesra Alam or MSMA was first implemented by the Department of Irrigation and Drainage (DID). Its control-at-source concept to guarantee zero development impact in both quantity and quality of runoff has revolutionized urban stormwater management in Malaysia. As highlighted in the manual, a succesful implementation of its principles and techniques though calls for involvement of various professionals including engineers, urban planners, environmental scientists, landscape architects and other professionals. Apart from civil engineers, not much is known about the other professionals involvement or awareness of MSMA. In light of this, this paper discusses the findings of a survey carried out to assess the levels of awareness, understanding and involvement of urban planning professionals in the implementation of MSMA. Questionnaires designed to assess the levels of awareness, understanding and involvement of the urban planning professionals in MSMA were distributed to randomly-selected urban planning professionals from government agencies and private firms. The study distributed a total of 150 questionnaire sets from which 92 were returned, giving a response rate of about 61%. The responses were then tabulated and analyzed using the Statistical Package for Social Sciences (SPSS) software and MS Excel spreadsheet. The tabulated results revealed that majority of the respondents were aware of MSMA and many claimed that they understood MSMA. However, upon further probing many of those who claimed to understand MSMA failed to correctly answer some basic questions about it. While some respondents may have been involved in the works that required using MSMA guidelines, their involvement were however superficial at best. Overall, majority of the respondents agreed that there was a general lack of awareness and understanding of MSMA among planning professionals, and they attributed this to a variety of reasons.